Value of Histogram of Gray-Scale Ultrasound Image in Differential Diagnosis of Small Triple Negative Breast Invasive Ductal Carcinoma and Fibroadenoma - Xu M; Li F; Yu S; Zeng S; Weng G; Teng P; Yang H; Li X; Liu G (Cancer Management and Research, 2022)
Maolin Xu,1,* Fang Li,2,* Shaonan Yu,1,* Shue Zeng,2,* Gaolong Weng,2 Peihong Teng,1 Huimin Yang,1 Xuefeng Li,3 Guifeng Liu1 1Department of Radiology, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Ultrasound, Hubei Cancer Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Department of Anesthesiology, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuefeng Li, Department of Anesthesiology, China-Japan Union Hospital of Jilin University, Xiantai Street, Changchun, 130033, People’s Republic of China, Email lixuefeng@jlu.edu.cn Guifeng Liu, Department of Radiology, China-Japan Union Hospital of Jilin University, Xiantai Street, Changchun, 130033, People’s Republic of China, Email gfliu@jlu.edu.cnObjective: To investigate the value of gray-scale ultrasound (US) image histogram in the differential diagnosis between small (≤ 2.00 cm), oval, or round triple negative breast invasive ductal carcinoma (TN-IDC) and fibroadenoma (FA).Methods: Fifty-five cases of triple negative breast invasive ductal carcinoma (TN-IDC group) and 57 cases of breast fibroadenoma (FA group) confirmed by pathology in Hubei cancer hospital from September 2017 to September 2021 were analyzed retrospectively. The gray-scale US images were analyzed by histogram analysis method, from which some parameters (including mean, variance, skewness, kurtosis and 1st, 10th, 50th, 90th and 99th percentile) can be obtained. Intraclass correlation coefficient (ICC) was used to evaluate the inter observer reliability of histogram parameters. Histogram parameters between the TN-IDC and FA groups were compared using independent Student’s t-test or Mann-Whitney U-test, respectively. In addition, the receiver operating characteristic (ROC) curve analysis was used for the significant parameters to calculate the differential diagnosis efficiency.Results: All the histogram parameters showed excellent inter-reader consistency, with the ICC values ranged from 0.883 to 0.999. The mean value, 1st, 10th, 50th, 90th and 99th percentiles of TN-IDC group were significantly lower than those of FA group (P < 0.05). The area under ROC curve (AUC) values of mean and n percentiles were from 0.807 to 0.848. However, there were no significant differences in variance, skewness and kurtosis between the two groups (P > 0.05).Conclusion: Histogram analysis of gray-scale US images can well distinguish small, oval, or round TN-IDC from FA.Keywords: ultrasound, histogram, triple negative breast cancer, fibroadenoma